The continuation rates of long‐acting reversible contraceptives in UK general practice using data from The Health Improvement Network. (24th September 2014) - Cea Soriano, Lucía; Wallander, Mari‐Ann; Andersson, Susan; Filonenko, Anna; García Rodríguez, Luis Alberto
Abstract Purpose The purpose of this study was to determine the continuation rates of new users of long‐acting reversible contraceptive (LARC) methods in the UK, using data from general practice. Methods We conducted an observational study using a general practitioner (GP) database, The Health Improvement Network (THIN). The methods studied were copper intrauterine devices (Cu‐IUDs), levonorgestrel‐releasing intrauterine system (LNG‐IUS), progestogen‐only implants and progestogen‐only injections. The study population comprised women in THIN aged 18–44 years during the period 2004–2009 who had been registered with their GP for at least 5 years, with a computerized prescription history of at least 1 year. Using computer algorithms, the database was searched for the Read and Multilex codes for each LARC method. New LARC users were identified and followed until there was a record indicating termination of use or the study period ended. Results The proportion of women who discontinued use during the same year of administration was 7.5% for Cu‐IUDs, 10.6% for LNG‐IUS, 13.2% for progestogen‐only implants and 54.4% for progestogen‐only injections. By the end of the study, a higher proportion of Cu‐IUD and LNG‐IUS users (21.1 and 18.6%, respectively) undertook consecutive use of the same method than progestogen‐only implant users (10.7%). Manual review of computerized profiles demonstrated the validity of this approach. Conclusions In the UK, the continuation rates of LARCs are high, and approximately one fifth of women chose to have a second intrauterine device fitted after expiry of the first device. A validation step demonstrated the reliability of the methodology and computer algorithms used. Copyright © 2014 John Wiley & Sons, Ltd.